Incorporating Islamic Principles into Early Childhood Education (ECE) Practices - Lailatul Mukarromah; Yunita Dwi Erawati; Nailul Mufida (Al-Qalam Institute, 2025)
This study aimed to analyze the integration of Islamic values and a holistic approach in early childhood education. Character development has been emphasized as a national education priority in Indonesia, where education is mandated to produce individuals with intelligence, personality, and noble morals. Previous studies have shown that embedding Islamic principles into teaching fosters respect, empathy, and discipline among children, while a holistic approach supports balanced cognitive, emotional, and spiritual growth. This research employed a qualitative descriptive method, with data collected through observation, interviews, and documentation, then analyzed using Miles and Huberman’s interactive model. Findings revealed that first, teachers perceived Islamic values as essential for nurturing children’s behavior, emotional regulation, and social interaction. Second, the curriculum at Dewi Masyithoh III Kindergarten demonstrated flexibility, allowing educators to embed values seamlessly into classroom activities while maintaining academic objectives. Third, challenges were identified, particularly in the availability of teaching resources and professional development for teachers, indicating the need for systemic support to sustain value-based education. These findings align with previous research yet extend the discussion by highlighting practical integration within a holistic framework. The study contributes insights for curriculum improvement and recommends enhanced teacher training and resource provision.